(untitled) (Third Sector Social Economic Review, 2025)
Communication can be defined as the process of transferring people’s feelings, thoughts and information from one mind to another. The most effective element that helps communication to take place in this process is language. The individual, who has been in communication with the world since the mother’s womb, acquires the language of the family in which he/she lives. Afterwards, in order for the individual to use the language correctly and effectively, the individual must go through an education and training process. In language teaching processes, it is essential to acquire four basic language skills. Language skills, which we divide into two groups as comprehension and expression, constitute the basis of language teaching. It is important to provide an interactive teaching environment for the acquisition of these complementary skills. Metaphors, which can be defined as the use of one concept instead of another concept for the purpose of analogy, guide us in the language education process. Foreign/second language learners who are not as proficient in the target language as native speakers can also explain the concepts they learn with various metaphors. This study aims to reveal Turkish as a foreign language learners’ perceptions of writing and speaking skills through metaphors and to analyze these metaphors by categorizing them. The study utilized a phenomenological approach, which is one of the qualitative research methods. The study group consisted of 49 students at B1, B2 and C1 levels who learn Turkish at Ankara Hacı Bayram Veli University Language Teaching Application and Research Center (DİLMER). “Metaphor Form for Writing and Speaking Skills” was used to collect the data. In this form, the participants were asked to fill in the personal information section and complete the sentences “Turkish writing skill is similar to ... because ...” and “Turkish speaking skill is similar to ... because ...”. The participants were informed about the subject before filling out the interview form. The data obtained were analyzed by content analysis technique. According to the data, it was seen that the learners developed metaphors in 6 categories for writing skills and 5 categories for speaking skills. In the study, it was determined that the learners produced mostly positive metaphors for speaking and writing skills and were willing to learn Turkish.